A Strategy for the Successful Management of Dermatofibrosarcoma Protuberans. Issue 1 (January 2015) - Goldberg, Carolyn; Hoang, Don; McRae, Matthew; Chung, Connie; Leffell, David J.; Narayan, Deepak
<x xml:space="preserve">Abstract</x> Background Dermatofibrosarcoma protuberans (DFSP) is a rare, locally invasive soft tissue sarcoma with extensive subclinical involvement. The National Comprehensive Cancer Network guidelines recommend immediate reconstruction in most cases. Our study reviewed the methods of treatment of DFSP at our institution, examined the types of closure used after surgical excision, and analyzed the prevalence of positive margins on permanent pathology after immediate closure after conventional non-Mohs excision of DFSP. Methods The charts of 25 patients treated with surgical excision and 16 with Mohs surgery from 1990 to 2009 for lesions consistent with DFSP were reviewed for clinical variables including disease state, tumor site, closure type, permanent pathology margin status, disease recurrence/persistence, and excisional margin size. Results The trunk, followed by the head and neck, were the most common sites for DFSP. No patients had distant metastasis at diagnosis or experienced recurrence in either the surgical excision or the Mohs surgery group. Twelve (48%) patients were found to have positive margins after initial surgical resection. All lesions treated with Mohs surgery had clear histological margins at completion. Average margin size for surgical excision patients was 2.33 cm (range, 0.75–4.5 cm), and 1.36 cm (range, 0.74–2.55 cm) for Mohs excision. The average duration of follow-up was 107.9 months. Conclusions The extent of DFSP is difficult to determine intraoperatively with traditional surgical excision, which leads to a higher rate of positive margins. Considering this difficulty and the complications of reconstruction with positive margins, we believe that reconstruction after tumor resection should be dependent on definitive pathologic clearance of the tumor.